Research progress on the mechanisms of apolipoprotein E in Alzheimer’s disease - Jiayuan Li; Ting Liu; Shengxi Meng (Guoji laonian yixue zazhi)
Alzheimer’s disease (AD) is a degenerative disorder of the central nervous system that predominantly affects the elderly.The Apolipoprotein E (ApoE) gene is identified as the most significant genetic factor associated with AD.This article reviews current findings on the relationship between ApoE and AD, the impact of APOE gene polymorphisms on AD, the interaction between ApoE and other pathogenic factors, and the role of ApoE in AD.Additionally, it discusses the diagnosis and treatment of AD to enhance the understanding of its pathogenesis and to provide new perspectives for the prevention and management of the disease.